Some issues of educational reform by Turkestan Jadids (Acta Education, 2025)
This article analyzes the reforms in the field of education of the Jadid movement, which took shape in the territory of Turkestan in the late 19th - early 20th centuries. It highlights the Jadids’ initiatives in establishing “new method” schools, their work on enriching educational programs based on modern sciences, and their ideas calling the younger generation to enlightenment